Tonic Upgaze in Infancy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
Tonic upward ocular deviation without seizure activity or neurologic disease is reported in 3 infants from the Pediatric and Neuro-ophthalmology Units, School of Medicine, University of California, San Francisco.